Deuteration of the farnesyl terminal methyl groups of δ-tocotrienol and its effects on the metabolic stability and ability of inducing G-CSF production. Issue 11 (1st June 2020) - Liu, Xingui; Gao, Zhengya; Fu, Qiang; Song, Lin; Zhang, Peiyi; Zhang, Xuan; Hendrickson, Howard; Crooks, Peter A.; Zhou, Daohong; Zheng, Guangrong
Graphical abstract: Abstract: δ-tocotrienol (DT3), a member of vitamin E family, has been shown to have a potent radio-protective effect. However, its application as a radioprotectant is limited, at least in part, by its short plasma elimination half-life and low bioavailability. In an effort to increase the metabolic stability of DT3, a deuterium substituted DT3 derivative, d6 -DT3, was designed and synthesized. d6 -DT3 showed improved in vitro and in vivo metabolic stability compared to DT3. The unexpected lower potency of d6 -DT3 in inducing granulocyte-colony stimulating factor (G-CSF) production in mouse revealed that the metabolite(s) of DT3 might play a major role in inducing G-CSF induction.